Vasorelaxation effect of Syzygium polyanthum (wight) walp. Leaves extract on isolated thoracic aorta rings of normal and hypertensive rats - Ismail, Azlini; Wan Ahmad, Wan Amir Nizam (IIUM Medical Journal Malaysia, 2016)
Introduction: Syzygium polyanthum (Wight) Walp. leaves are traditionally consumed by the Malays as an alternative treatment for hypertension. Until now, effect of S. polyanthum leaves extract on blood vessel is not yet disclosed. Methods: This study investigated the effect of S. polyanthum leaves aqueous extract (AESP) (0.01, 0.1, 1 & 10 mg/ml) on isolated thoracic aorta rings of normotensive Wistar-Kyoto rats (WKY) and Spontaneously Hypertensive rats (SHR). Both rings were pre-contracted using phenylephrine (1 µM). Distilled water that dissolved AESP served as negative control. Results: As compared to negative control, AESP at 0.1, 1, and 10 mg/ml significantly relaxed aorta rings of WKY by 39.81 ± 2.99 % (P<0.001), 59.55 ± 7.60 % (P<0.001), and 72.58 ± 5.57 % (P<0.001), respectively. In SHR, AESP at 1 and 10 mg/ml significantly relaxed the aorta rings of SHR by 40.53 ± 3.66 % (P<0.001) and 65.73 ± 8.24 % (P<0.001), respectively. There was a significant difference between AESP-induced vasorelaxation in WKY and in SHR at a concentration of 0.1 mg/ml (P<0.001). The IC50 value for AESPinduced vasorelaxation on aorta rings of WKY (94.67 ± 1.41 µg/ml) was lower than of SHR (799.80 ± 1.69 µg/ml). Conclusions: The S. polyanthum leaves extract was able to cause significant relaxation on aorta rings of both normal and hypertensive rats. Thus, this finding is well-corroborated with the use of this plant as a traditional remedy for hypertension. It is suggested that an in-depth investigation of the mechanism of vasorelaxation of this plant is carried-out in the future.